Design of planar meander line antenna - Dalila, Misman; Mohamad Zoinol A, Abd Aziz; M. N., Husain; Soh, Ping Jack (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org